2002
DOI: 10.1021/jp025783k
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of the Valence Ionization Intensities of Chemical Functional Groups between Molecules

Abstract: The transferability of the valence ionization intensities of chemical functional groups is investigated with three common laboratory ionization sources (Ne IR, 16.7 eV; He IR, 21.2 eV; and He IIR, 40.8 eV) for a series of molecules. Each molecule contains two different functional groups that are well separated electronically and spatially by an alkane chain linker. The optimum length of the alkane chain between the functional groups is investigated. In this initial study, the functional groups are RCl, RBr, RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This method qualitatively models the effect of orbital delocalization on the intensities . Lichtenberger and colleagues have demonstrated that this approach reasonably describes the cross sections associated with the low-kinetic-energy electrons obtained from sources such as helium(I) and helium(II) . Because the thorium ketimido molecular orbitals (MOs) exhibit significant f atomic orbital (AO) character and the Th formally has a 7 s 2 6 p 6 6 d 2 atomic electron configuration, no atomic f AO cross section is available for Th.…”
Section: Methodsmentioning
confidence: 99%
“…This method qualitatively models the effect of orbital delocalization on the intensities . Lichtenberger and colleagues have demonstrated that this approach reasonably describes the cross sections associated with the low-kinetic-energy electrons obtained from sources such as helium(I) and helium(II) . Because the thorium ketimido molecular orbitals (MOs) exhibit significant f atomic orbital (AO) character and the Th formally has a 7 s 2 6 p 6 6 d 2 atomic electron configuration, no atomic f AO cross section is available for Th.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, relative intensities of bromine, chlorine, and iodine lone pair bands decrease significantly on going from HeI to HeII radiation. Such changes are caused by variations of atomic photoionization cross-sections and are well substantiated by theoretical and UPS studies. These known intensity variations have often been used as an important assignment aid.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 65%